Ultra‐hyper‐fractionated radiotherapy for high‐grade gliomas. Issue 12 (8th November 2021) - Frosina, Guido; Fontana, Vincenzo; Verzola, Daniela; Rosa, Alessandra; Gaggero, Gabriele; Garibotto, Giacomo; Vagge, Stefano; Pigozzi, Simona; Daga, Antonio
Abstract: High‐grade gliomas (HGGs; WHO grades III and IV) are invariably lethal brain tumors. Low‐dose hyper‐radiosensitivity (HRS) of HGG is a well‐established phenomenon in vitro . However, possibly linked to the unavailability of accurate animal models of the diseases, this therapeutic effect could not be consistently translated to the animal setting, thus impairing its subsequent clinical development. The purpose of this study was to develop radiotherapeutic (RT) schedules permitting to significantly improve the overall survival of faithful animal models of HGG that have been recently made available. We used primary glioma initiating cell (GIC)‐driven orthotopic animal models that accurately recapitulate the heterogeneity and growth patterns of the patients' tumors, to investigate the therapeutic effects of low radiation doses toward HGG. With the same total dose, RT fractions ≤0.5 Gy twice per week [ultra‐hyper‐fractionation (ultra‐hyper‐FRT)] started at early stages of tumor progression (a condition that in the clinical setting often occurs at the end of the guidelines treatment) improved the effectiveness of RT and the animal survival in comparison to standard fractions. For the same cumulative dose, the use of fractions ≤0.5 Gy may permit to escape one or more tumor resistance mechanisms thus increasing the effectiveness of RT and the overall animal survival. These findings suggest investigating in the clinical setting the therapeutic effect of an ultra‐hyper‐FRT schedule promptly extending the conventional RT component of the current guideline ("Stupp") therapeutic protocol. Abstract : A human high‐grade glioma (VIPI) positive for the stem cell marker nestin implanted in the brain of an immunodeficient mouse is irradiated with total 10.0 Gy split in 4 × 2.5 Gy fractions (hypofractionated radiotherapy) or 30 × 0.25 + 20 × 0.125 Gy fractions (ultra‐hyper‐fractionated radiotherapy). Mice treated with the latter survive significantly longer.